FATORES CRÍTICOS DE SUCESSO DE START UP DE VEÍCULOS E A QUALIDADE (CMMI) NO DESENVOLVIMENTO DE PRODUTOS NO SUL FLUMINENSE - Rocha, Henrique Martins (2005)
This research is intended to validate the critical success factors for automotive products start-up. Those critical success factors have been identified through Porter s prognostics for new product launching and/or through studies from Daniel and Rockart for the American automotive industry along the years 60-80. The theoretical referential used in this research were Rockart s critical success factors, Porter s life cycle model and the capability maturity model for integrated product and process development from SEI (Software Engineering Institute Carnegie Mellon University). Having the existing literature about the subject and prognostic deductions as start points for this study, five critical success factors have been identified and validated through research and a questionnaire applied in two automaker plants in the Southern State of Rio de Janeiro, Brazil. As part of the same research, the capability maturity level for product evelopment has been measured for each organization, based on the CMMI (Capability Maturity Model Integration) evaluation criteria.